Cultivar evaluation and trait analysis of tropical early maturing maize under Strigainfested and Strigafree environments - Badu-Apraku, Baffour; Akinwale, R. (Elsevier, 2011)
Striga hermonthica is a major constraint to maize (Zea mays L.) production in sub-Saharan Africa. The use of secondary traits that have high heritability and genetic correlation with grain yield can improve the precision with which Striga resistant genotypes are identified. Fifteen early cultivars were evaluated under Striga-infested and Striga-free conditions for 2 years at Mokwa and Abuja, Nigeria. The objective was to examine their performance based on multiple traits under stress and non-stress conditions and analyze the interrelationship among traits using genotype-by-trait (GT) biplot so as to assess the value of traits used in the base index for selection for Striga resistance and improved grain yield (YLD). TZE-W DT STR C4 had the best performance based on multiple traits while TZE-W DT STR C4, TZE-Y DT STR C4, Multicob Early DT, and TZE-W DT STR QPM C0 were the closest to the ideal cultivar when Striga infested. Ears per plant, Striga damage at 8 and 10 weeks after planting, and ear aspect (EASP) were the most reliable traits for selecting for resistant genotypes. Striga emergence count at 8 and 10 weeks after planting were not among the reliable traits identified for selection for improved grain yield and their inclusion in the base index needs to be further verified. EASP had high correlation with grain yield and was one of the most reliable traits for selection for increased grain yield under Striga infestation and should be included in the index.